Jack London's women - Stasz, Clarice (Book collections on Project MUSE., 2001)
"At age twenty-three, Jack London (1876-1916) sold his first story, and within six years he was the highest paid and most widely read writer in America. To account for his success, he created a fiction of himself as the quintessential self-made man. But as Clarice Stasz demonstrates in this absorbing collective biography, London always relied on a circle of women who nurtured him, sheltered him, and fostered his legacy." "Using newly available letters and diaries from private collections, Stasz brings this diverse constellation of women to life. London was the son of freethinking Flora Wellman, yet found more maternal comfort from freed slave Jennie Prentiss and his stepsister Eliza. His early loves included a British-born consumptive, a Jewish socialist, and an African American woman. His first wife, Bess Maddern, was a teacher and devoted mother to daughters Bess and Joan, while his second, Charmian Kittredge, shared his passion for adventure and served as a model for many characters in his writings. Following his death, the various women who survived London both promoted his legacy and suffered the consequences of being constantly identified with a famous man."--Jacket.